Aplikasi Streptomyces sp. ASR 67 dan Pupuk Organik Cair dalam Mengendalikan Penyakit Layu Fusarium oxysporum dan Pemacu Pertumbuhan Tanaman Kentang (Solanum tuberosum L.) Varietas Granola - Diharjo, Dewi; Fatmawati, Umi (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Demand for the Granola variety of potatoes continues to increase, but its productivity is not yet sufficient for market needs. This is due to the wilt disease attack on potatoes caused by the fungus Fusarium sp., thereby reducing potato productivity. The aim of this research was to determine the use of liquid culture of Streptomyces sp. ASR 67 and liquid organic fertilizer as an organic anti-fungal in controlling wilt disease caused by Fusarium oxysporum on potato plants (Solanum tuberosum L.). The research was carried out using a Randomized Group Design (RAK) method using five treatments. Each treatment was repeated five times and each repetition used one potato plant. Treatment was given by watering the potato growing medium for 30 days, which was done every three days. The results showed that administration of liquid culture of Streptomyces sp. ASR 67 10% combined with liquid organic fertilizer (1:9) was able to increase plant growth with the parameters of height, number of leaves, number of stems, weight of tubers significantly, while POC 2% and Streptomyces sp. ASR67 (1:1) is able to reduce the incidence of wilt disease best.